Correlation between Chronic Kidney Disease Severity and Cognitive Function - Surbakti, Epa Danisa; Fitri, Fasihah Irfani; Rambe, Aldy Safruddin (Jurnal Kedokteran Brawijaya, 2021)
Chronic kidney disease (CKD) is an independent risk factor for cognitive impairment in all domains, especially delayed memory and executive function. The purpose of this study was to determine the correlation between chronic kidney disease severity and cognitive function. This study used a cross-sectional design in stage III, IV, and V CKD patients in the Nephrology Polyclinic of Haji Adam Malik Central General Hospital. Cognitive function tests were performed using the Montreal Cognitive Assessment (MoCA INA), digit span, and Trail Making Test A & B. The Spearman test was used to analyze the correlation between CKD severity and cognitive function. This study involved 45 chronic kidney disease patients consisting of 28 (62.2%) males and 17 (37.8%) females with a mean age of 49.67Â±12.18 years. The results of statistical analysis showed that there was a significant positive correlation between CKD on the MoCA-INA examination (r=0.618, p=<0.001), FDS (r=0.414, p=0.005), there was a significant negative correlation on the TMT A time examination (r=-0.425, p=0.004), TMT A error (r=-0.497, p=0.001), TMT B time (r=-0.618, p=<0.001), TMT B error (r=-0.370, p=0.012). The results of this study prove a significant correlation between the severity of CKD and cognitive function.